Penggunaan Electric-Fencing Dalam Usaha Meminimalisir Konflik Antara Gajah dan Manusia Di Desa Salah Sirong Jaya, Kabupaten Bireuen - Kamil, Puspita Annaba; Fajriyani, Fajriyani; Desfandi, Mirza; Azis, Daska; Ridha, Syahrul (Bansigom Na Publisher, 2025)
Conflict between elephants and humans is a serious problem in Salah Sirong Jaya Village, Bireuen Regency, Aceh. These conflicts have an impact on crop damage, loss of community income, and threats to elephant and human safety. This study aims to evaluate the effectiveness of the use of electric fencing in minimizing these conflicts. This study uses a descriptive qualitative method through in-depth interviews and direct observation. The results of the study show that the installation of electric fences is able to significantly reduce the frequency of conflicts between elephants and humans. People feel safer and productivity increases. However, the long-term effectiveness of electric fencing depends on regular maintenance, financial support, and active participation of the community. With proper management, electric fencing is a sustainable solution in mitigating elephant-human conflicts, while maintaining the balance of the ecosystem